PENINGKATAN KEMAMPUAN MEMBACA PESERTA DIDIK KELAS 2 SDN BANJARSUGIHAN 1/116 MELALUI MEDIA CERITA BERGAMBAR DALAM PEMBELAJARAN BAHASA INDONESIA - Tanti Nur Rosyada; Vicky Dwi Wicaksono; Titik Indriyani; Rini Nawangsari; Kasmiatun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The motivation for this research stems from the lack of reading ability shown by class II students at SDN Banjarsugihan 1/116 on the topic of Indonesian. This research uses CAR methodology which includes two research cycles. The process consists of three stages: planning (Plan), implementation cycle (Do), and reflection (See). The research participants consisted of 25 class II students at SDN Banjarsugihan for the 2023-2024 academic year, including 13 female students and 12 male students. Research findings show that cycle I had a completion rate of 73.52%, with the number of students who successfully completed the classical learning program being 10 people or reaching 40% of the total. Meanwhile, there were 15 students who did not complete, namely 60% of the total students. In cycle II, there was an increase in learning outcomes. Specifically, the results of the assessment of class II children at SDN Banjarsugihan in cycle II showed an average of 84%. There were 22 students who completed and 3 students did not complete. The level of completion of classical learning in cycle II was 86.66%, while the number of evaluations that had not been completed was 12%. Based on these findings, it can be concluded that the use of a problem-based learning paradigm with the use of innovative SAS learning media can improve academic achievement and reading ability in class at SDN Banjarsugihan.